Avaliação das causas de condenações de perus (Meleagris gallopavo) em 2005 e 2006 no estado do Rio Grande do Sul - Schlestein, Aline (2007)
In Brazil, in 2006, 35.650.000 turkeys were slaughtered, totalizing 353,278 ton, 156,056 were exported generating a cambial prescription of US$ 262.820.985, 00. Objecting evaluate the occurred convictions in turkeys slaughter in the Rio Grande do Sul were evaluated the spread sheets of turkeys conviction under fiscalization in the Rio Grande do Sul ´s Federal Supervision (RS), in the period of January of 2005 until December of 2006. The results demonstrates that almost of the eight million turkeys carcasses (7.984.528 birds), 19.9% had some kind of postmortem condemnation. Most condemnations were partial 1.539.939 (97.1%) and 46,628 (2.9%) were totally condemned. The principal causes of partial condemnations were: contusion/breaking (7.025%), abscess (3.698%), contamination (2.942%), callus of chest (1.995%), arthritis (1.428%), airsacculitis (1.101%), dermatosis (0.937%) and excessive scald (0.056%). The causes of total postmortem condemnation were: repugnant aspect (0.255%), wasting (0.085%), excessive scald (0.077%), airsacculitis (0.040%), colibacillosis (0.033%) and contamination (0.025%). It was observed that the most of these condemnations are related to the imperfections in the transport and in the slaughter process of these animals showing the necessity of improvements, as corrective actions that can minimize bruises, harm bleeding, like others.